Obstetrical outcome valuations by patients, professionals, and laypersons: differences within and between groups using three valuation methods - Bijlenga Denise; Birnie Erwin; Mol Ben WJ; Bonsel Gouke J (BMC, 2011)
Abstract Background Decision-making can be based on treatment preferences of the patient, the doctor, or by guidelines based on lay people's preferences. We compared valuations assigned by three groups: patients, obstetrical care professionals, and laypersons, for health states involving both mother and (unborn) child. Our aim was to compare the valuations of different groups using different valuation methods and complex obstetric health outcome vignettes that involve both maternal and neonatal outcomes. Methods Patients (n = 24), professionals (n = 30), and laypersons (n = 27) valued the vignettes using three valuation methods: visual analogue scale (VAS), time trade-off (TTO), and discrete choice experimentation (DCE). Each vignette covered five health attributes: maternal health ante partum, time between diagnosis and delivery, process of delivery, maternal outcome, and neonatal outcome. We used feasibility questionnaires, Generalization theory, test-retest reliability and within-group reliability to compare the valuation patterns between groups and methods. We assessed relative weights from each valuation method to test for consistency across groups. Results Test-retest reliability was equal across groups, but different across methods: highest for VAS (ICC = 0.61-0.73), intermediate for TTO (ICC = 0.24-0.74) and lowest for DCE (kappa = 0.15-0.37). Within-group reliability was highest in all groups with VAS (ICC = 0.70-0.73), intermediate with DCE (kappa = 0.56-0.76) and lowest with TTO (ICC = 0.20-0.66). Effects of groups were smaller than effects of methods. Differences between groups were largest for severe health states. Conclusion Based on our results, decision making among laypersons should use TTO or DCE; patients should use VAS or TTO.